A ética do cuidar e educar na primeiríssima infância - MIRANDA, Thayná Marcely Guimarães de (2020)
The present study focuses on the ethics of caring and educating in early childhood. It aims to contribute to the understanding of care as ethics as synonymous with the in separability of caring for and educating infants and Young children. It brings together conceptions about care and the child and how they have manifested from the eighteenth century to the current context. It traces a historical panorama about the conceptions of care and children, as well as using records that present qualitative data collected in a daycare center in the peripheral district of Belém: Unit of Early Childhood Education Wilson Bahia, thad had as subjects of investigation the group the Maternal IB and the irrespective teachers. The methodology used consist do faction research, thus, analysis was performed from records, based on the bibliographica l survey about the care that reverberates in the day care center. To do so, the first section was developed for conceptions of care and the evolution of this term concomitant with the conception of infant and toddler. Since care whit the sehas a greater focus on child care centers, a second section was built to present care in the instituition. At the end, the results are presented in a fourth section, after the methodology, where one can observe some atitudes of care with the small, in the dependencies of UEI Wilson Bahia. Thus, care is now manifested as ethics, while attending to the physical need infants and Young children.